2018
DOI: 10.1007/s00706-017-2085-7
|View full text |Cite
|
Sign up to set email alerts
|

Benzil/triethylamine: a photo-reducing system for Cu2+

Abstract: We have investigated the photo-induced reduction of Cu2+–Cu0 using benzil/triethylamine mixtures. The formation of elemental Cu is indicated by the appearance of its characteristic plasmon absorption peaks at 515 nm and 620 nm. Importantly, the nature of the counterion of the Cu2+ salt affects the reduction process. In the presence of Cl−, the reduction proceeds faster than with SO42-. Photo-induced electron transfer between excited benzil and triethylamine leads to the benzil radical anion, which acts as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…This reaction requires water as solvent, a pH range between 1–7, and rather long irradiation times (>1 h) to give good yields. Elemental analysis indicated that one BAPO‐OH molecule possibly serves as four electron reductant surpassing the efficiency of aromatic ketones and α‐hydroxyketones as photo‐reducing agents [23,48–52] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction requires water as solvent, a pH range between 1–7, and rather long irradiation times (>1 h) to give good yields. Elemental analysis indicated that one BAPO‐OH molecule possibly serves as four electron reductant surpassing the efficiency of aromatic ketones and α‐hydroxyketones as photo‐reducing agents [23,48–52] …”
Section: Introductionmentioning
confidence: 99%
“…Elemental analysis indicated that one BAPO-OH molecule possibly serves as four electron reductant surpassing the efficiency of aromatic ketones and α-hydroxyketones as photo-reducing agents. [23,[48][49][50][51][52] We have recently identified the delocalized ketyl-type radical (C * ), which is rapidly formed from the primary radical phosphanoyl radical P * (Scheme 1). [53] Because the SOMO of C * is relatively high in energy, this electron-rich radical serves as an electron donor (reducing agent).…”
Section: Introductionmentioning
confidence: 99%